The Relationship Between Corporate Governance and Integrated Reporting - Hayyin Agustina Mawardani; Iman Harymawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: The objective of this research is to investigate the level of integrated reporting information disclosure in the annual reports of non-financial public listed companies in Indonesia Stock Exchange (IDX) during 2017 to 2018, as well as its relationship with corporate governance that measured by the independent board, the board size, board gender diversity, and types of the external audit firm, whether a corporate audited by Big-4 accounting public firm or non-Big-4 accounting public firm.Design/Methodology/Approach: In this research, the authors utilized a total of 936 observations. The analysis used in this research is using the Ordinary Least Square (OLS) Regression.Research findings: This research showed that corporations with a higher number of independent board members and a bigger board size are disclosing a higher level of integrated reporting information. However, the authors did not find a significant correlation between board gender diversity and audit firm types on the level of Integrated Reporting information disclosure.Theoretical contribution/ Originality: This research contributes to adding to the literature of integrated reporting disclosure theory.Practitioner/Policy implication: Hopefully, the findings can give the policy-maker a comprehensive picture of the relationship between corporate governance and integrated reporting disclosure.Research limitation/Implication: The limitation of this paper is the measurement of Integrated Reporting disclosure that was conducted using content analysis by word count was done manually which may contain subjectivity of the authors.